2020
DOI: 10.2147/cmar.s235519
|View full text |Cite
|
Sign up to set email alerts
|

<p>Pretreatment Systemic Inflammation Response Index in Patients with Breast Cancer Treated with Neoadjuvant Chemotherapy as a Useful Prognostic Indicator</p>

Abstract: Background and Objective: Systemic inflammation response index (SIRI=N×M/L), based on neutrophil (N), monocyte (M), and lymphocyte (L) counts, is used to predict the survival of patients with malignant tumors and can fully evaluate the balance between host immune and inflammatory condition. The present study is aimed to evaluate the potential prognostic significance of SIRI in patients with breast cancer undergoing neoadjuvant chemotherapy. Subjects and Methods: A total of 262 breast cancer patients treated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 43 publications
(41 reference statements)
1
31
1
Order By: Relevance
“…In addition, in postmenopausal women with breast cancer, Hua et al reported that patients with low SIRI had significantly longer OS than those with high SIRI [ 32 ]. Consistently, Chen et al observed that among patients with breast cancer treated with NAC, those with low SIRI had longer DFS and OS, but they did not find a statistical correlation between SIRI and pCR, which contradicts our results [ 11 ]. In patients with breast cancer, different ages, stages and phenotypes also correspond to different immune responses, therefore leading to different SIRIs.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…In addition, in postmenopausal women with breast cancer, Hua et al reported that patients with low SIRI had significantly longer OS than those with high SIRI [ 32 ]. Consistently, Chen et al observed that among patients with breast cancer treated with NAC, those with low SIRI had longer DFS and OS, but they did not find a statistical correlation between SIRI and pCR, which contradicts our results [ 11 ]. In patients with breast cancer, different ages, stages and phenotypes also correspond to different immune responses, therefore leading to different SIRIs.…”
Section: Discussioncontrasting
confidence: 92%
“…The systemic inflammation response index (SIRI) is an integrated indicator based on the counts of peripheral venous blood neutrophils, monocytes and lymphocytes that might reflect the status of the local immune response and systemic inflammation [ 10 ]. To date, the relationship between SIRI and pCR has rarely been reported [ 11 ]. SIRI was first reported by Qi et al for its ability to predict the survival of patients with pancreatic cancer [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, our study showed that both platelet and monocytes are not different between IPF patients and healthy controls, and combined indexes do not perform better than NLR. The latters have shown better predictive abilities than NLR, in acute clinical conditions and malignancies [10,14,37,38]; this probably means that in cases of chronic inflammation adaptive phenomena prevent the increment of specific other than neutrophil and lymphocyte cell populations and stabilize their turnover. As a result, combined indexes may not be more effective than NLR in chronic systemic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence has shown that systemic immune response markers are promising prognostic biomarkers for various cancers. The combined indicators of neutrophils, lymphocytes, monocytes, and platelets, such as NLR ( 18 , 19 ), PLR ( 20 ), SII ( 21 , 22 ) and SIRI ( 23 , 24 ), have been reported to be predictive of cancer prognosis. SIRI is a new systemic inflammatory response biomarker based on neutrophil, monocyte, and lymphocyte counts.…”
Section: Discussionmentioning
confidence: 99%